The relationship between gather tendency with families and the self-awareness of flood hazard: the case of Sumida Ward, Tokyo - Yen-Yu Chang; Hiroko Imaizumi; Ching-I Chen; Meng-Cong Zheng; Kiminobu Sato (Journal of Asian Architecture and Building Engineering)
This study investigated the level of flood knowledge, shelter familiarity, self-awareness in different situations, and the tendency to gather with family members during flooding. Results based on 161 participants aged 8–88 years. Participants’ own age was a predictor of whether or not they would gather with their families during the evacuation. Participants’ familiarity with the shelter was associated with knowledge, and increased interest in the shelter surroundings increased knowledge, which increased self-awareness of disaster response. Including family members in evacuation planning significantly increases participants’ awareness and involvement, leading them to plan their routes carefully. In addition, the results of the study revealed information about the expectations of Sumida residents during a flood: the safety of family members was ranked as the priority, and from this, it was possible to know the methods or means of escape that should be included about family members when evacuating. Followed by information on electricity and water facilities, which is relevant to the judgment of whether or not to go to a shelter. Then, information on flooding in the home area is needed. These findings can inform the design of effective flood information systems and community preparedness programs in urban areas.